Konstruksi Hukum Ddalam Pengaturan Pengelolaan Hutan yang Berkearifan Lokal di Kabupaten Buleleng Provinsi Bali - Rideng, I Wayan; Arya Wijaya, I Ketut Kasta; Putu Budiartha, I Nyoman; Riberio, Leonito (Universitas Negeri Malang, 2022)
This study aims to describe models of local wisdom forest management and legal constructions in local wisdom forest management. This study uses an empirical legal approach with a descriptive research type. Data collection techniques were carried out through interviews, observation, and documentation studies. Determination of the sample in this study using a purposive sampling technique and all data was analyzed qualitatively. The results of the study show that the local wisdom forest management model includes the reconstruction and revitalization of the role of forest village communities facilitated by the government by practicing the principles of good governance. Local wisdom that exists in all villages in Buleleng Regency is used as a reference in forest management. Legal construction in forest management in Buleleng Regency accommodates local wisdom values which are believed to provide welfare for customary law communities and the realization of forest sustainability